2017
DOI: 10.1111/dom.13037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of liraglutide on dietary lipid‐induced insulin resistance in humans

Abstract: Aims: To test whether liraglutide suppresses postprandial elevations in lipids and thus protects against high saturated fatty acid (SFA) diet-induced insulin resistance. Methods:In a randomized placebo-controlled crossover study, 32 participants with normal or mildly impaired glucose tolerance received liraglutide and placebo for 3 weeks each. Insulin suppression tests (IST) were conducted at baseline and after a 24-hour SFA-enriched diet after each treatment. Plasma glucose, insulin, triglycerides and non-est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Since 2005, the long-acting glucagon-like peptide-1 (GLP-1) receptor agonist, liraglutide, has been approved for the treatment of patients with type 2 diabetes mellitus (T2DM). Epidemiological studies and animal experiments have shown that GLP-1 receptor agonists have pleiotropic effects that may enhance their therapeutic effect in patients with T2DM, including the promotion of insulin secretion, the inhibition of gastric emptying, reduction in body weight, the increase in pancreatic β-cell mass, and the reduction in glucagon production [ 3 , 11 ]. Insulin glargine, a long-acting insulin analog, has been widely used in the treatment of T2DM [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since 2005, the long-acting glucagon-like peptide-1 (GLP-1) receptor agonist, liraglutide, has been approved for the treatment of patients with type 2 diabetes mellitus (T2DM). Epidemiological studies and animal experiments have shown that GLP-1 receptor agonists have pleiotropic effects that may enhance their therapeutic effect in patients with T2DM, including the promotion of insulin secretion, the inhibition of gastric emptying, reduction in body weight, the increase in pancreatic β-cell mass, and the reduction in glucagon production [ 3 , 11 ]. Insulin glargine, a long-acting insulin analog, has been widely used in the treatment of T2DM [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Western blots also did not show downregulation of key inflammatory pathways, such as JNK, NFĸB and ERK in adipose tissue. There was a slight decline in the protein levels of TxNIP, a master stimulatory protein of inflammation, insulin resistance and apoptosis, that have been demonstrated to be downregulated with GLP‐1 receptor agonists . Furthermore, there was a trend for increased expression of the adpq gene that encodes adiponectin, an adipokine with well described insulin‐sensitizing and anti‐inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…Microvascular vasodilation was measured in arterioles isolated from subcutaneous abdominal adipose tissue biopsies. Up to six arterioles per sample were isolated, cannulated and pressurized to 60 mmHg pressure without flow, as previously described . Using a videomicroscope (VIA‐100, Boeckeler, Tucson, AZ, USA), the vessels were pre‐constricted to ∼60% of maximum diameter with endothelin‐1 and then treated with increasing doses of insulin (0.02, 0.2, 2 and 20 nM), followed by 10 mM papaverine, 4 min per step.…”
Section: Methodsmentioning
confidence: 99%
“…Metformin or other compounds are also used to lower TXNIP aortic levels in vivo or endothelial levels in vitro in order to restrain NLRP3 activation and protect from endothelial dysfunction and cardiovascular risk factors [60,67,87,[91][92][93][94][95][96][97][98][99][100][101]. The regulation of the NLRP3 inflammasome by the TRX-TXNIP complex is believed to be controlled by Nrf2 and AMPK [60,[102][103][104]106,107]. The overexpression of TXNIP activates the TLR4-NF-κB-NLRP3 inflammasome signaling pathway with increased MyD88, NLPR3 inflammasome, and ASC expression, as well as the increased phosphorylation of lκBα and p65, thus promoting downstream NF-κB activation [109].…”
Section: Txnip: Link Between Oxidative Stress and Inflammationmentioning
confidence: 99%